2012
DOI: 10.3390/ijms130810537
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aptamer-Protein Complexes by X-ray Crystallography and Alternative Approaches

Abstract: Aptamers are oligonucleotide ligands, either RNA or ssDNA, selected for high-affinity binding to molecular targets, such as small organic molecules, proteins or whole microorganisms. While reports of new aptamers are numerous, characterization of their specific interaction is often restricted to the affinity of binding (KD). Over the years, crystal structures of aptamer-protein complexes have only scarcely become available. Here we describe some relevant technical issues about the process of crystallizing apta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 70 publications
0
43
0
1
Order By: Relevance
“…No evidence for self-association was found; the hetero-association data proved the availability of exactly two equivalent and independent binding sites on SA for APT, K D  = 190 nM. The latter result suggests that SA acts as a dimer of dimers where APT may bind to the cleft site, as confirmed by mass spectroscopy (Ruigrok et al 2012).
Fig.
…”
Section: Resultsmentioning
confidence: 81%
“…No evidence for self-association was found; the hetero-association data proved the availability of exactly two equivalent and independent binding sites on SA for APT, K D  = 190 nM. The latter result suggests that SA acts as a dimer of dimers where APT may bind to the cleft site, as confirmed by mass spectroscopy (Ruigrok et al 2012).
Fig.
…”
Section: Resultsmentioning
confidence: 81%
“…The challenges surrounding the solution of crystal structures of aptamer-protein complexes were reviewed (8). Although a number of RNA aptamer/protein complex structures have been solved, only the thrombin-aptamer (9-12) and Von Willebrand Factoraptamer complexes (13) have been solved for a DNA aptamer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated the extraordinary potential of sensor devices constructed from aptamers, single‐stranded DNA or RNA molecules attached to nanoparticles or nanotubes . These “aptasensors” combine the unique optical and electrical properties of the nanomaterials with the ability of aptamers to bind with high affinity and specificity to predefined targets . Targets include specific proteins and small molecules like 17β‐estradiol (E2).…”
Section: Introductionmentioning
confidence: 99%
“…To engineer a reliable sensor for the selective and sensitive detection of molecules like E2, it is advantageous to have a thorough understanding of aptamer binding properties at the molecular level. Crystal structures of aptamer‐target complexes provide detailed information on molecular interactions, and thus a thorough understanding of binding . Structures providing the coordinates of all atoms may be obtained by techniques such as X‐ray crystallography, and nuclear magnetic resonance .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation